THE ROLE OF GREEN SUKUK IN SUSTAINABLE FINANCING: AN ANALYTICAL STUDY IN INDONESIA DURING THE 2018–2024 PERIOD - Jojo Jojo; Ana Frasipa (STIESA Press, 2025)
This study aims to analyze the role of green sukuk in supporting sustainable financing in Indonesia. Green sukuk is a sharia-compliant financial instrument specifically designed to finance environmentally friendly projects. This study uses a descriptive-qualitative approach with secondary data analysis from the Ministry of Finance, the Financial Services Authority (OJK), and international institutions. The results show that green sukuk contributes significantly to financing renewable energy, sustainable transportation, and energy efficiency projects in Indonesia. However, challenges remain in terms of transparency, retail investor participation, and regulatory harmonization. This study provides strategic recommendations for the government and Islamic finance industry players to optimize the potential of green sukuk going forward.